A new species of Fageapseudes (Crustacea: Peracarida: Tanaidacea) from California, with comments on the systematics of the family Apseudidae - Drumm, David T.; Bamber, Roger N. (Zootaxa, 2013)
Examination of material housed at the Los Angeles County Museum of Natural History revealed a new species of Fageapseudes from 4100 m depth off California, the first record of the genus in the eastern North Pacific. Fageapseudes pluma n. sp. is very similar to the Japanese species Fageapseudes brachyomos Bamber, but can be distinguished by differences in setation and by having fewer articles in the antennal flagellum and uropodal exopodite. It is unique for the genus and subfamily in having the inner caudo-distal seta of the maxillipedal endite “feather-like” instead of “leaf-like” or simply setulose. Problems with the current classification of the Apseudidae are briefly discussed, and new diagnoses are established for the subfamily Leviapseudinae and the genus Fageapseudes.